New therapies in the treatment of overactive bladder. (September 2013) - Yeo, Eu Kiang Sharon; Hashim, Hashim; Abrams, Paul
Abstract : Introduction: Overactive bladder (OAB) is a common condition which affects both men and women across many age groups with significant impact on quality of life. There is currently an armamentarium of treatment options available ranging from conservative, medical therapy to radical surgeries. Increasing understanding of OAB is resulting in the rapid development of new therapies today. Areas covered: The purpose of this article was to summarise the latest developments in non-neurogenic OAB treatment, discuss the evidence and results of current and new treatment modalities available through review of published data and results presented at recent international meetings. Expert opinion: The ultimate goal in OAB therapy is to provide good clinical efficacy, safe, non-invasive and easy to administer. There is definitely room for development of new therapies in OAB and current progress is encouraging.